Kajian Penulisan Teks Akademik Bagi Mahasiswa Terhadap Peningkatan Keterampilan Menulis - Asianna Manik; Devi Putri Thesia; Elsa Prida Br Tarigan (Universitas Palan, 2024)
Essays or essays and students, whether at elementary, intermediate, or higher levels, often produce poor results. Many mistakes are made regarding spelling, word choice, and sentence structure. Many students do not understand scientific texts and their rules. This misunderstanding These misconceptions are very seriously researched considering the efforts of the government, educational institutions, including universities, to improve the culture of research in the academics. This research uses a qualitative method with the type of approach in the form of a library study. The results of the research It was found that the factors that cause difficulties in writing scientific papers are, for example, the low motivation of students in writing, lack of confidence and in writing, lack of confidence and lack of mood, low interest in reading, low student curiosity, and students' understanding of scientific papers that are not good scientific writing as well as low mastery of the writing the rules of writing.